Perceptions of climate change among Grade 11 learners in the Tshwane Metropolitan Municipality, South Africa - Mapaleng Silas Lekgeu; Nerhene Davis (Environmental Association of Southern Africa, 2017)
Of all the environmental problems facing humankind today, anthropogenic-induced climate change is regarded as one of the most damaging in its potential repercussions. For this reason, the perceptions of climate change among high-school learners, who represent future decision-makers and stand as a proxy for the next generation, are of importance. This study was designed so as to gain insight into the nature of perceptions and associated determinants among Grade 11 learners in the Tshwane metropolitan municipal area. Specifically, it probed dynamics between the content in the formal curriculum (Curriculum and Assessment Policy Statement or CAPS) and learners' exposure to electronic media, their peers and parents (their arenas of social interaction) in forming these perceptions. The study involved a qualitative analysis of 68 questionnaires completed by learners from two high schools. Findings include misconceptions regarding climate change among learners, as they conflate climate change and the greenhouse effect. The learners' perceptions seem to be shaped by the cumulative outcomes of dynamics between different arenas of exposure and influence (formal education, peers, parents and the media). It is argued that learners' perceptions about climate change fostered in formal education should also be understood in the context of their potential exposure to: (1) alarmist framings of climate change in the media; (2) conceptual disagreements in the climate change research community; and (3) the influence of peers and parents. Rather than avoiding the dynamics from contesting and diverging 'arenas of exposure', future climate change education planning should accommodate and align contending views that might influence the learning process.